Borderline Experiences and Transformation: The Narrative of Mountain Experience in Mihail Sebastian’s Novel "The Accident" (1940) - Cotârlea, Delia (Universitatea Transilvania Brasov, 2025)
Since the Middle Ages, the relationship between the individual and the mountain has been interpreted as a sensual and introspective experience of the world, becoming a central motif within mountain narratives. Simultaneously, physical exertion and the overcoming of dangers in alpine settings have been portrayed as instruments for liberating the individual from societal constraints and as pathways to personal transformation. For renowned alpinists such as Reinhard Karl and Lynn Hill, mountaineering signifies a return to the self, where the subjective inner world stands in deliberate contrast to the realities of everyday life and is experienced as a source of happiness and fulfillment. Within this context, the concept of resonance with the mountains gains prominence, suggesting that an intense engagement with nature opens new experiential spaces in which individuals can enter a profound dialogue with themselves and the world. Against this background, the present article undertakes an analysis of Mihail Sebastian’s novel "The Accident".
Keywords: Carpathians; Mountaineer; Transformation in the Mountains; Resonance; Mihail Sebastian; The Accident